2022
DOI: 10.1029/2022jc018815
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Interannual Eddy Kinetic Energy Variability in the Sulawesi Sea Revealed by OFAM3

Abstract: Mesoscale eddies play a vital role in oceanic mass and heat transport and bridge the energy transfer between large-scale and mesoscale (submesoscale) dynamics (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…And finally, returning to the central topic of this study, the effects of mesoscale eddy activities on the residence time and pathway of the ITF, we recognize that the limited length of the particle tracking experiments does not provide information on how the effects may change on an interannual time scale. Hao et al (2022) found that the interannual variability of eddy kinetic energy in the Sulawesi Sea is primarily modulated by transport from the MC intrusion that controls the intensity of barotropic instability within the Sulawesi Sea. The MC intrusion, in turn, is influenced by the paths of the MC and NGCC (and its undercurrent) as well as eddy activities in the western Pacific.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…And finally, returning to the central topic of this study, the effects of mesoscale eddy activities on the residence time and pathway of the ITF, we recognize that the limited length of the particle tracking experiments does not provide information on how the effects may change on an interannual time scale. Hao et al (2022) found that the interannual variability of eddy kinetic energy in the Sulawesi Sea is primarily modulated by transport from the MC intrusion that controls the intensity of barotropic instability within the Sulawesi Sea. The MC intrusion, in turn, is influenced by the paths of the MC and NGCC (and its undercurrent) as well as eddy activities in the western Pacific.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Hao et al. (2022) found that the interannual variability of eddy kinetic energy in the Sulawesi Sea is primarily modulated by transport from the MC intrusion that controls the intensity of barotropic instability within the Sulawesi Sea. The MC intrusion, in turn, is influenced by the paths of the MC and NGCC (and its undercurrent) as well as eddy activities in the western Pacific.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These currents have the potential to transport microplastics from one area to another, potentially leading to their dispersion over considerable distances within the sea (Iskandar et al, 2021). Furthermore, the circular currents in the western part of the Sulawesi Sea are believed to be associated with the activity of eddies in the region (Masumoto et al, 2001;Hao et al, 2022). Eddies may potentially contribute to the transport of materials, including microplastics, within the water column and thus could redistribute the microplastics around Miangas and Talaud Islands.…”
Section: Discussionmentioning
confidence: 99%